Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s11044-013-9342-2
|View full text |Cite
|
Sign up to set email alerts
|

Super-element global modal parameterization for efficient inclusion of highly nonlinear components in multibody simulation

Abstract: Over the last decades, higher and higher accuracy is expected from flexible multibody models. Accurate flexibility descriptions and detailed contact algorithms have been mostly developed with this aim. In practice, linearized models are often used at the expense of severe accuracy loss in order to improve simulation times. Several multibody packages have also been developed for the simulation of nonlinear components, but these typically lead to elevated simulation times. Alternatively, a cosimulation with a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…This is due to the nonlinear relationship between global and local frame coordinates. To reduce this nonlinearity, a generalised modal reduction method based on the absolute coordinate formulation (ACF) with a constant mass matrix was proposed in Pechstein et al 23 and Naets and Desmet 24 There, FFRF-based and ACF-based superelements were compared, and it was concluded that the ACF-based element is more efficient and accurate. It was even found that in some cases, the results given by the FFRF-based superelement were not dependable.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the nonlinear relationship between global and local frame coordinates. To reduce this nonlinearity, a generalised modal reduction method based on the absolute coordinate formulation (ACF) with a constant mass matrix was proposed in Pechstein et al 23 and Naets and Desmet 24 There, FFRF-based and ACF-based superelements were compared, and it was concluded that the ACF-based element is more efficient and accurate. It was even found that in some cases, the results given by the FFRF-based superelement were not dependable.…”
Section: Introductionmentioning
confidence: 99%
“…Only the forceelements which are acting on the relative rigid DOFs θ i are considered as internal forces. The reduced internal forces F q i int are also obtained by projecting the unreduced (nonlinear) internal forces F x int onto the reduced DOFs, similar to the process described in [28]:…”
Section: Equations Of Motion For Sub-modelsmentioning
confidence: 99%
“…In [24,25] a component-level reduction method based on an enhanced Craig-Bampton method is described. The other way around, the system-level based formulations employ a global reduction of rigid and elastic components [7,22,32,34]. Recently, the component mode synthesis (CMS) techniques have been employed to condense all the elastic coordinates, thereby obtaining an equivalent rigid-body model [19].…”
Section: Introductionmentioning
confidence: 99%